DAMPAK PENGELUARAN PEMERINTAH BIDANG PARIWISATA DAN BELANJA WISATAWAN TERHADAP PERTUMBUHAN EKONOMI PROVINSI SUMATERA UTARA - , MARISI DUMA TAMBA; , Dr. Budiono Sri Handoko, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development and itâs growth is one of the key to show that the tourism industry can be used as a supporting sector of the economic improvement. The tourism which include in some sectors can be used as a reference to develop the leading sector. This study aims to: (1) analyze the relationship of the tourism sector with other sectors of the economy